(untitled) (International Journal of Food and Nutritional Sciences, 2022)
Attention Deficit Hyperactivity Disorder (ADHD) is neurodevelopmental Disorder that affects 10% of school age children. These children suffer from low self-esteem, troubled relationships and academic backwardness. Teachers have very little knowledge in identifying, assessing, monitoring and reporting of the disorder. Aim: The present study focuses on the comparative perception of children exhibiting ADHD symptoms by teachers from Government aided and private aided and unaided schools. Material and Methods: This study was conducted in different Government, Private aided and unaided Schools in Karnataka, India with a sample size of 500 from 37 schools. Random sampling method was utilized with a descriptive study design. Conner’s scale was administered to teachers to identify children exhibiting ADHD symptoms. The data was analyzed by applying one-way Anova, Pair wise comparison followed by Tukey’s Multiple Post-hoc Procedures test. Results and conclusion : There is significant difference between teachers of Government, Private aided and Private unaided schools with respect to inattention, hyperactivity, impulsivity symptoms. No significant difference was perceived between male and female teachers. Hence the teachers’ knowledge regarding ADHD has to be promoted. Teachers have to be assisted in gaining knowledge and misconceptions about ADHD with management solutions through collaborative partnership. An evidence-based in-service education can improve teachers attitude and increase their understanding of the symptoms exhibited to assess the child’s educational strengths and weakness at the early stages of development.